Towards a Semantic Prosodies Approach in the Study of Irony - Benna, Sameh (JOURNAL OF ADVANCES IN LINGUISTICS, 2014)
The advent of large corpora such as the LOB, Brown¦made it possible for readers to perceive consistencies in the influence of collocation on the behaviour of particular linguistic forms. Irony as a stylistic phenomenon procedure relies heavily and draws its effect from a collocative clash. However, in order to be able to identify a potential collocative clash, there must be a sufficiently consistent background of expected collocation against which the depiction of irony becomes clear. The consistent meaning that a form has is referred to in this paper as semantic prosody. Semantic prosodies proved to be largely unaccessible to human intuition about language and they cannot be deduced reliably through introspection. In this paper irony in Hemingways A Farewell to Armswas depicted using a collocational approach. The BNC corpus will be used to depict the semantic prosody of some words in the novel and how through their collocates they yield an ironical meaning.